Strength and water retention behavior of loess stabilized with guar gum and fiber under dry and wet cycles - Xinxin Du; Hao Tian; Xin Kang; Zengchun Sun; Xiaoxiao Zhao; Yucong Ren (Scientific Reports)
Abstract To improve the mechanical and water-retention behavior of loess and reduce the erosion failure caused by dry–wet cycles, the applicability of guar gum (GG) biopolymer and basalt fiber in the solidification of loess is investigated. The addition of GG can enhance the compressive strength and disintegration resistance of loess. When the GG content is 0.5%, 1.0%, and 2.0%, the compressive strength of stabilized loess increased by 30.15%, 67.85%, and 124.8%, respectively. The shear strength of GG–fiber stabilized loess is obviously higher than that of specimens without GG, and the higher the GG content, the stronger the shear resistance. The dry–wet cycles have a significant degradation effect on untreated and GG–fiber stabilized loess. After 8 dry–wet cycles, the cohesion and internal friction angle of the specimen containing 2.0% GG decreased by 45.90% and 10.74%, respectively. As the GG content increases, the water-retention capacity of stabilized is enhanced, but the dry–wet cycles have a significant deterioration effect. Furthermore, the soil water characteristic curves prediction model for GG–fiber stabilized loess is established by considering the effect of dry–wet cycles and GG content, and the prediction results are basically consistent with the measured data (R 2 = 0.92). This study confirmed the feasibility of applying guar gum and basalt fiber to improve soil strength, water stability, and water-retention capacity, and provided a basis for engineering construction and soil erosion control in the loess area.